The missing tooth - Cole, Joanna; Hafner, Marylin (New York : Random House, 1988)
Best friends Arlo and Robby are almost identical in what they wear, what they like, and even where they have teeth missing, but when Robby insists on betting on who is going to lose the next tooth their friendship is endangered.
"Grades 1-3"--Cover.
260
260
Accelerated Reader AR
Keywords: Friendship -- Fiction; Teeth -- Fiction